Gene expression profiling by mRNA sequencing reveals dysregulation of core genes in Rictor deficient T-ALL mouse model. (December 2019) - Hua, Chunlan; Chen, Xiangyu; Yuan, Weiping; Li, Yang; Yu, Jing; Li, Haijun; Ming, Liang
Highlights: We obtained 1475 DEGs associated with differentiation and transcription. We obtained 46 core genes with high network degree and fold change. We obtained 10 crucial genes which significantly associated with survival. Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is a neoplastic disorder with peak incidence in children and young adults. The mTOR complex is an important component of the PI3K/Akt/mTOR signaling cascade and holds great promise for the treatment of hematopoietic malignancies. Previous studies have shown that the depression of Rictor, one of the components of the mTOR complex, prevents myeloproliferative disorders and leukemia However, knowledge of the progression of mTOR has not greatly improved the prognosis of T-ALL. To identify potential prognostic biomarkers for T-ALL, a whole-genome expression profile of Rictior deficient T-ALL mice was performed. As a result, 1475 differentially expressed genes (DEGs) were identified. Network analysis revealed 46 genes with a high network degree and fold-change value. Kaplan-Meier analysis identified ten crucial genes which significantly associated with survival in Rictor deficient T-ALL mice. These findings provide potential therapeutic targets in leukemia and bear immediate relevance to patients with leukemia.